Initiating Sustainable Agriculture through Local ‘Sleman’ Longan Cultivation and Stingless Beekeeping in the Sinduadi Farmers Group - Adib Fakhruddin Yusuf; Dian Sartika; Vida Rahma Latifah; Karso Suryo Putro; Novia Noor Rachmawati; Prima Sekti Kusnanda; Tiara Amelia Putri; Budi Setiadi Daryono; Tri Joko; Ignatius Sudaryadi (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2026)
Sinduadi Village, located in Mlati Subdistrict, Sleman Regency, Special Region of Yogyakarta, Indonesia, is home to several active horticultural farmer groups. Among their commodity crops, longan cultivation in Sinduadi Village has faced persistent constraints, particularly low productivity. To address this limitation, a community service program was initiated to introduce a superior local variety, the ‘Sleman’ longan. This cultivar was developed through sustained research and breeding by the Laboratory of Genetics and Breeding, Faculty of Biology, Universitas Gadjah Mada (UGM). Stingless bees, locally known as klanceng bees, play an important role as pollinators in horticultural systems. Integrating longan cultivation with stingless beekeeping as a managed pollination strategy is expected to improve longan productivity and support more sustainable farm management. The program applied a comprehensive capacity building approach, including lectures, extension sessions, hands-on training, and regular monitoring. These activities aimed to strengthen both conceptual understanding and practical competence related to cultivation of the ‘Sleman’ longan variety and stingless beekeeping management. The program resulted in an observable improvement in participants’ knowledge and skills within the Sinduadi Village farming group. Improvements in farmer capacity will be evaluated through continued monitoring of field practices and performance over time. Although short-term gains in yield have not yet been observed, substantial longer-term benefits are anticipated as the plants establish, adapt, and enter stable production. Overall, this knowledge transfer is expected to empower the community to address local agricultural constraints more independently and to promote sustained improvements in livelihood and well-being.